How we developed the GIM clinician–educator mentoring and scholarship program to assist faculty with promotion and scholarly work. (1st February 2015) - Bertram, Amanda; Yeh, Hsin Chieh; Bass, Eric B.; Brancati, Frederick; Levine, David; Cofrancesco, Joseph
Abstract: Clinician Educators' (CEs) focus on patient care and teaching, yet many academic institutions require dissemination of scholarly work for advancement. This can be difficult for CEs. Our division developed the Clinician–Educator Mentoring and Scholarship Program (CEMSP) in an effort to assist CEs with scholarship, national reputation, recognition, promotion and job satisfaction. The key components are salary-supported director and co-director who coordinate the program and serve as overall mentors and link CEs and senior faculty, and a full-time Senior Research Coordinator to assist with all aspects of scholarship, a close relationship with the General Internal Medicine (GIM) Methods Core provides advanced statistical support. Funding for the program comes from GIM divisional resources. Perceived value was evaluated by assessing the number of manuscripts published, survey of faculty regarding usage and opinion of CEMSP, and a review of faculty promotions. Although impossible to attribute the contributions of an individual component, a program specifically aimed at helping GIM CE faculty publish scholarly projects, increase participation in national organizations and focus on career progression can have a positive impact.